Peran Kepuasan Konsumen dalam Memediasi Pengaruh Harga, Citra Merk, dan Kualitas Produk Terhadap Minat Beli Ulang Produk Scarlett di Timika - Ohoimas, Nandika Yuda Pratama; Madmuar, Daud B.; Jabir, Ansar Putra Iryanti; Nifanngeljau, Johanis (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The method used in this study is quantitative, the data used is primary data. Data collection techniques used in this study are observation, interviews and questionnaires. The population used in this study was 63. The sampling technique used in this study was using the total sampling technique, where the total population was used as a sample. Therefore, the number of samples used in this research was 63 respondents. The data analysis technique used is path analysis, a statistical method used to analyze the causal relationship between variables in a model, which is assisted by using SPSS 26 Software. The results found in this study are that price has an effect and is not significant on the interest in repurchasing Scarlett Products in Timika City, their image has an effect and is not significant on the interest in repurchasing Scarlett Products in Timika City, product quality has an effect and is not significant on the interest in repurchasing Scarlett Products in Timika City, consumer satisfaction has a significant effect on the interest in repurchasing Scarlett Products in Timika City, price has an effect on buying interest, but is unable to mediate consumer satisfaction towards the interest in repurchasing Scarlett Products in Timika City, their image has an effect on buying interest, but is unable to mediate consumer satisfaction towards the interest in repurchasing Scarlett Products in Timika City, product quality has an effect on buying interest, but is unable to mediate consumer satisfaction towards the interest in repurchasing Scarlett Products in Timika City.